Implementasi Merdeka Belajar melalui Praktik Kewirausahaan Berbasis Digital Masa Pandemi Covid 19 - Sukardi Sukardi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
This study aims to develop a model for implementing merdeka belajar (i.e., freedom to learn; independent learning) through digital-based entrepreneurship development practices in the entrepreneurship-supporting industry during the Covid 19 pandemic. This research uses a design-based research method, which is divided into 4 stages, namely: identification and problem analysis, development of program prototypes, program prototype trial and implementarion, and reflection on the design principles. This study focuses on the second stage, which is developing merdeka belajar prototypes through digital entrepreneurship practices using reverse design. The research subjects in this study were students studying humanities and social science majors at the University of Mataram, who were all taken using purposive sampling. In addition, business actors were also involved as informants. The research instrument used observation sheets, project-based assessments, and interviews. Data from the results of the study were analyzed qualitatively. The results of the study show that there are three components in the implementation of merdeka belajar through digital-based entrepreneurial practices, namely; digital-based business design; digital-based batik entrepreneurial products; and digital-based jewelry entrepreneurial products. Students are able to develop products and product-marketing innovations through digital marketing by utilizing various online platforms so that they can support the existence of their business during the Covid 19 pandemic.